MAHALLIY BUDJET DAROMADLARINI SHAKLLANTIRISHNING ILMIY-NAZARIY ASOSLARI (Marketing Journal, 2026)
AbstractThe article analyzes the scientific and theoretical foundations of forming localbudget revenues. The structure of revenue sources, their legal framework, and themechanism of intergovernmental fiscal relations were examined. The role of localtaxes, shared national taxes, and transfers in shaping the revenue base was assessed.Based on data for 2020-2024, the dynamics of local budget revenues and expenditureswere reviewed. The importance of tax potential and forecasting in strengtheningregional financial independence was substantiated. Directions for expanding therevenue base, improving tax administration, and identifying new revenue sourcesthrough the mahalla system were defined.Keywords: local budgets, expanding the revenue base, budget, incentivization,socio-economic development, local taxes.